ONLINE LEARNING POLICY EVOLUTION STUDY: BIBLIOMETRIC ANALYSIS - Rethorika Berthanila, Rethorika; Yulianti, Rachmi; Marthalena, Marthalena; Purnama, Indra Nizar (Universitas Negeri Yogyakarta, 2023)
This study aims to analyze the scientific literature on online learning policies, from the first published paper (2001) to the present (2022) through bibliometric analysis and visualization by utilizing the Scopus database-based VOSviewer software. This study took 384 articles from international authors that focused on the topic of policy online learning. Articles are classified according to the year of publication, author country, co-author, affiliation, keywords and journal title. Furthermore, articles are examined based on several indicators, including the contribution of the state/institution/author. Journal distribution, heavily cited articles, bibliographic coupling and keyword analysis. The search results show that the United States serves as the country of origin of the most prolific author affiliation in publishing articles, the Department of Early Childhood Education, The Education University (Hong Kong) serves as the home of the most prolific author affiliation, and Agaton CB, from The Open University (United States), is considered the most prolific writer. In addition, the Sustainability (Switzerland) Journal is the source of the most discussed publication topics in its journals. Furthermore, Impacts of the Covid-19 Pandemic on Life of Higher Education Students: A Global Perspective is considered the article with the most references. In addition, the most widely discussed topics are online learning policies, e-learning, public education policies, educational policies, sustainable development, digital technologies teaching and learning, mobile learning, blended learning, and distance education.